PENGENDALIAN HAYATI PENYAKIT LAYU FUSARIUM PADA TANAMAN TOMAT (Solanum lycopersicum L.) MENGGUNAKAN BAKTERI ENDOFIT ASAL TANAMAN LIAR - NERU SATRAH, VIT; ASDAR, ASDAR; KHAERUNI, ANDI; SANTIAJI BANDE, LA ODE; RAHMAN, ABDUL; ISNAINI ULFA, NUR; ARIYANTI, EKA LESTARI (Jurnal Agroteknos, 2023)
This research aims to determine the effect of using endophytic bacteria from wild plants in the biological control of Fusarium Wilt disease on tomato plants and to find out which isolate method is best for controlling Fusarium Wilt disease on tomato plants. The research was carried out at the Plant Protection Laboratory, Phytopathology Unit, and Experimental Garden Greenhouse 1, Faculty of Agriculture, Halu Oleo University, Kendari, from September to November 2022. This research used a Randomized Block Design (RBD) with 5 treatments repeated 3 times for a total of 15 treatment units. The variables observed were divided into 2, namely vegetative plant growth (plant height, number of leaves, and number of productive branches) and the incidence of Fusarium Wilt disease on tomato plants. The data was analyzed using variance and if there was a real influence, it was continued with the Duncan Multiple Range Test (DMRT) at a confidence level of 95%. The results of the research showed that endophytic bacteria from wild plants were able to increase plant growth and control Fusarium Wilt disease in tomato plants and ASR-3(2) isolate was the best isolate in increasing plant growth and controlling Fusarium Wilt disease.